Penguatan Kapasitas Kelompok Sadar Wisata (Pokdarwis) dalam Mendukung Pengembangan Bumdes untuk Pengelolaan Amenitas Desa Agrowisata Alam Berbasis Bambu di Desa Pardomuan Ajibata Kecamatan Ajibata Kabupaten Toba - Junjungan Saut Bonar Pangihutan Simanjuntak; Henry Sitorus (Universitas Medan Area, 2023)
The humanism approach as a movement raises awareness of human values aimed at the students of Bina Agung Private Middle School, Sunggal District, with the aim that students can avoid the dangers of drugs and promiscuity both within the school environment and outside the school environment. The implementation method is carried out by lectures and discussions with students. The results of this community service show that the humanist approach to students is very effectively used as a means to make changes in the mental revolution of students to avoid the dangers of drugs and promiscuity, because this can interfere with learning and reduce student achievement at school. In addition to the humanism approach that is applied to students, it is also carried out with a preventive approach to students by providing an understanding of the dangers of drugs and promiscuity and accompanied by teachers